STRATEGY OF STRENGTHENING SPIRITUAL QUALITY INCUPPING AND RUQYAH SERVICES TOWARDS CUSTOMER SATISFACTION: A QUALITATIVE STUDY AT THE BEKAM RUQYAH CENTER SOREANG BRANCH - Febby Andini; Yoki Oktorian Sukardi (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the application of spiritual quality in cupping and ruqyah services and identify strategies for improving spiritual quality implemented at the Soreang Branch of the Bekam Ruqyah Center. The problems identified were customer dissatisfaction related to limited service space and a less than optimal religious atmosphere that affected comfort during therapy. This study used a descriptive qualitative approach with data collection techniques through in-depth interviews, participant observation, and documentation. While data validity was strengthened by triangulation of sources, methods, and theories with the help of NVivo 12 software and supplemented with a SWOT analysis. The results showed that the implementation of spiritual quality improvement was carried out by the presence of Islamic values, maintaining cleanliness, reciting prayers, and the therapist's empathetic attitude were important factors in fostering a sense of calm and comfort in customers. Implementing strategies for improving spiritual quality through therapist training, implementing SOPs based on Islamic law, and creating a supportive spiritual environment. However, limited service facilities and infrastructure still need to be addressed for improvement. Therefore, this study as a whole confirms that service quality that connects spiritual and physical aspects holistically contributes significantly to customer satisfaction.